PENGARUH LEADERSHIP STYLE TERHADAP KINERJA KEUANGAN MELALUI PERILAKU PEMILIK ATAS ISU MANAJEMEN LINGKUNGAN SEBAGAI VARIABEL INTERVENING - Sulistiyo, Agnes Sari (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to financial performance, leadership style to Owner Attitude of Environmental Management Issue, Owner Attitude of Environmental Management Issue to financial performance on firms in Surabaya and its surrounding area. This study also examined the indirect and significant relationship of leadership style to financial performance through Owner Attitude of Environmental Management Issue as the intervening variable on firms in Surabaya and its surrounding areas.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â This study used quantitative approach, whereas the data obtained through the distribution of questionnaires to firms in Surabaya and its surrounding area and then processed by using smartPLS software. The result showed that there was a positive and significant relationship of leadership style to financial performance, leadership styleÂ to Owner Attitude of Environmental Management Issue, Owner Attitude of Environmental Management Issue to financial performance on firms in Surabaya and its surrounding areas. The Ownerâs Attitude of Environmental Management Issue wasnât the effective intervening variable to leadership style and financial performance because the direct relationship between leadership style and financial performance gave larger affect than through Owner Attitude of Environmental Management Issue.